MAKNA SARANA UPACARA TUJUH BULANAN (TINGKEBAN) DI DESA JUBEL KIDUL KECAMATAN SUGIO KABUPATEN LAMONGAN (Jurnal Magister Hukum Perspektif, 2022)
This research is based on the community tradition of the Seven Monthly Ceremony (Tingkeban) for the people of Jubel Kidul Village, Sugio District, Lamongan Regency. People always carry out traditions from generation to generation. The purpose of this study was to determine the meaning contained in the means of the Seven Monthly Ceremony (Tingkeban) in Jubel Kidul Village society, Sugio district, Lamongan City. The formulation of the problem taken is what the means of the Seven Monthly Ceremony (Tingkeban) in Jubel Kidul Village, Sugio District, Lamongan Regency. This research uses juridical-empirical methods using qualitative methods in the form of data collection techniques using interview, observation, and documentation techniques. The results of this study indicate that the facilities for the Seven Months (Tingkeban) ceremony include Dila/ Lampu Ublek (smooth the birth process), Bunga Kenanga (God's favorite), Cengkir (not fighting with relatives), Rujak (take the good side), Kendi and Cobek (male symbol). -male and female), Procot (born with Procat-Procot), White and Red Porridge (pleasing people), Tumpeng (strong), Nasi Golong (rizkinya gemolong), Ketupat (remember with a partner), Lepet, Apem (isyarah a woman ), Eggs (pregnancy age), Pleret (baby in good condition), Pigeon (always remember the house), Polo Pendem (always remember that humans come from the ground), Pisang sepet (has a sweet personality). Keywords: Seven Monthly Ceremony (Tingkeban), Symbols, Meanings